2011
DOI: 10.1016/j.proeng.2011.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of passive and active drag in swimming

Abstract: In order to understand the physical origin of passive resistance in swimming the resistance breakdown for a swimmer is investigated. A combination of empirical methods and theoretical analysis is used to predict passive resistance in the speed range 0 – 2 ms-1 and is shown to provide similar results to those from experimental testing. Typical magnitudes of wave, viscous pressure and skin friction resistance contribute 59%, 33% and 8% of total passive resistance respectively at free swim speed. A comparison is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 5 publications
1
34
0
Order By: Relevance
“…There are a set of mathematical models that can be used to have some insight about a vessel hydrodynamics (e.g., sailing, canoeing, kayaking, surfing, rowing). Recently, that set of mathematical models was adapted to human swimming [ 13 ]. However, it remains to be shown how valid and reliable these procedures are.…”
Section: Introductionmentioning
confidence: 99%
“…There are a set of mathematical models that can be used to have some insight about a vessel hydrodynamics (e.g., sailing, canoeing, kayaking, surfing, rowing). Recently, that set of mathematical models was adapted to human swimming [ 13 ]. However, it remains to be shown how valid and reliable these procedures are.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has focused on quantifying the passive drag of a swimmer [2]. However, there has been less focus on quantifying the magnitude of wave resistance which contributes to the total passive drag that acts on a swimmer: 1. experimental techniques using a flume or towing swimmers or mannequins [15,1,13], 2. numerical simulations [16], and 3. analytical methods drawing from naval architectural techniques [17,13,14]. Of specific interest 90 is how these methods are employed to investigate the influence of wave resistance on the passive drag of a swimmer.…”
Section: Passive Resistance Of Swimmersmentioning
confidence: 99%
“…They also used k- model in 3D-CFD numerical simulation for calculating wall shear stresses near body and showed that the values will be increased in rigid body regions like head and shoulders of swimmer. Prediction of passive and active drag in swimming has been done by Webb (2011). He combined the empirical methods and theoretical analysis to predict passive resistance in the speed range up to 2 ms -1 and the results have been compared with experimental tests.…”
Section: Introductionmentioning
confidence: 99%